High-intensity and moderate-intensity interval training in heart failure with preserved ejection fraction: A meta-analysis of randomized controlled trials. Issue 8 (22nd February 2023) - Lai, Ping; Xue, Jin-Hua; Xie, Mu-Jin; Ye, Jin-Hua; Yang, Ning; Zhong, Yi-Ming; Liao, Yong-Ling
Abstract : Background: Exercise training significantly improves cardiorespiratory fitness (CRF) in heart failure with reduced ejection fraction (HFrEF) patients, but high-intensity interval training (HIIT) is not superior to moderate-intensity interval training (MIIT). Whether HIIT is more beneficial than MIIT in patients with heart failure with preserved ejection fraction (HFpEF) remains unclear. Methods: On August 29, 2021, we conducted a comprehensive computerized literature search of the Medline, EMBASE, Web of Science, and Cochrane databases using the following keywords: "HF or diastolic HF or HFpEF or HF with normal ejection fraction and exercise training or aerobic exercise or isometric exercises or physical activity or cardiac rehabilitation." Only randomized controlled trials (RCTs) reporting comparisons between HIIT and MIIT in HFpEF were included in the final analysis to maintain consistency and obtain robust pooled estimates. Methodological quality was assessed based on the ratings of individual biases. To generate an overall test statistic, the data were analyzed using the random-effects model for a generic inverse variance. Outcome measures were reported as an odds ratio, and confidence intervals (CIs) were set at 95%. The study followed PRISMA guidelines. Results: This meta-analysis included only RCTs comparing the efficacy of HIIT and MIIT in HFpEF patients. This study included 150 patients from 3 RCTs. In the current pooled data analysis, HIIT significantly improves diastolic function measured by E/A ratio (WMD, 0.13; 95% CI, 0.03–0.23, P = .009). However, no significant change was observed in the diastolic function measured by E/e' ratio (WMD, 0.39; 95% CI, −2.40 to 3.18, P = .78), and CRF evaluated by both VO2 (mL/kg per min; WMD, −0.86; 95%CI, −5.27 to 3.55, P = .70) and VE/CO2 slope (WMD, 0.15; 95% CI, −10.24 to 10.53, P = .98), and systolic function (EF-WMD, −2.39; 95% CI, −12.16% to 7.38%, P = .63) between HIIT and MIIT in patients with HFpEF. Conclusion: In HFpEF patients, HIIT may be superior to MIIT in improving diastolic function, measured by E/A, but not CRF and left ventricular systolic function.